Characterization And Corrosion Behaviour Of 96.5sn-3.0ag- 0.5cu Solder On Cu Substrate At Different Reflow Reactions - Lee , Liu Mei (2013)

(untitled)
96.5Sn-3.0Ag-0.5Cu (SAC305) thin film solder exhibits different surface characteristics if compared to conventional bulk solder. In thin film solder, the actual surface is comprised of intermetallic layers whereas in the case of conventional solder, the intermetallic layers happened at the interfacial region of solder/base metal. This in turn, resulted in different surface microstructure and chemical composition. Moreover, a subtle and unstudied aspect of SAC305 in thin film characteristics was limited. Thus, the effect of solder reflow conditions at various temperatures and times were investigated. Structural and elemental characterizations indicated that Sn, Ag3Sn, and Cu6Sn5 were present in the as-deposited SAC305 thin film on Cu substrate. After solder reflow, SAC305 thin film was totally reacted and developed into Cu6Sn5 then Cu3Sn. Cu6Sn5 is located almost exclusively in the volume, whereas Cu3Sn appears as a thin uniform layer structure beneath Cu6Sn5. The Cu3Sn intermetallic layer consistently increases with increased temperature but remains within the thickness of Cu6Sn5. The corrosion behavior of bare Cu, as-deposited SAC305/Cu and as-reflowed SAC305/Cu at varying reflow temperatures was investigated by means of potentiodynamic polarization in a 6 M potassium hydroxide (KOH) solution. Bare Cu was found to possess the best corrosion resistance, whereas the as-deposited SAC305/Cu had the lowest corrosion resistance. As-reflowed SAC305/Cu with an exposed Cu3Sn layer exhibited better corrosion resistance than did Cu6Sn5. All of the samples contained the corrosion products of oxide. Bare Cu obeys the well-known duplex structure of a Cu2O/CuO, Cu(OH)2 layer. For as-reflowed SAC305/Cu, the corroded surface was also mainly composed of SnO and SnO2.